Multilingual mathematics dictionary grade R - 6 - Department of Arts and Culture (Department of Arts and Culture, 2013)
MATHEMATICS School Projects In General The Terminology Coordination Section’s (TCSs) primary focus with the school projects is the documentation of existing terminology, and facilitation of the development of terminology in the African languages for new concepts that appear in the teaching materials for Grades 1 to 6. Eight learning areas are incorporated inCurriculum 2005. These learning areas are Mathematics, Natural Science and Technology, Human, Social, Economic and Management Sciences, Arts and Culture, Life Orientation and Languages. About this edition. This glossary of terms compiled by the TCS of a school subject in all the official languages is the first of its kind. Approximately 1 000 entries have been documented for this project. The team who worked on the terms considers it part of a learning process – also for themselves. The different collaborator groups, the team members of which are all first language speakers of the particular target languages, added term equivalents. Part of the process was to supply the collaborators with definitions and/or example sentences for the English terms. The terms were researched in different dictionaries and on the Internet, and sometimes a new definition was written which included elements of the different dictionaries that were consulted. All the dictionaries that were consulted in the research phase were meticulously acknowledged on the database. The aim of documenting the information in existing dictionaries and providing new definitions was to assist the collaborators in supplying the equivalents in the indigenous languages. In cases where there were no existing terms in the indigenous languages, a new term had to be coined. The definitions and example sentences are not included in this edition. It is planned that English definitions will be included in a following edition. Mathematics Since it may be argued that mathematical terms lie on a continuum the terminological data was collected from relevant teaching materials used in Grade 1 up to Grade 6. Mathematics is generally referred to as Numeracy Skills in Grades 1 to 3. In these grades a number of general terms such as match, choose, fill in, light, heavy etc. are included. To teach the learners about space and position many prepositions such as like, behind, on, under, etc. are included. Learners have to learn about measurements, capacity, height, weight, length, shapes, and patterns. In the context of Mathematics terms such as long, tall, wide, full, half-full and even cup (measurement: 250 ml) have a mathematical meaning, and are thus included in the list, although it might be argued that they are general words in other contexts. In order to read the time on a clock the learners need to know that hand may be used to indicate the hand of a clock (long hand, short hand) and they learn that even a clock has a face. Learners also have to learn how to use a calculator. It is sometimes difficult to decide on the status (general words or subject specific terms) of lexical items in school texts, and that is why many terms used in teaching Mathematics at primary level are regarded to be ordinary words, but are nevertheless included in the glossary. As from Grade 4 upwards the subject is generally referred to as Mathematics. Purely mathematical terms are limited. The bulk of the terms stay the same throughout the grades although vi the manner in which they are used becomes progressively more difficult for each consecutive learning phase.Terms such as triangle, circle, square and rectangle are already introduced on a very elementary level in the lower grades; the learners have only to recognise the shapes. We hope that these endeavours will encourage, and indeed also make a contribution towards mother-tongue education for all speech communities in SA. The Editorial Committee does not claim this product to be comprehensive or entirely without errors and scope for improvement. Feedback, especially on the layout, the accuracy of the equivalents and the comprehensiveness of the dictionary will be welcomed.
Department of Arts and Culture: Republic of South Africa
Keywords: Multilingual terminology